2019
DOI: 10.17576/jsm-2019-4807-03
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Land Use-Land Cover Changes in the Central Rift Valley of Ethiopia

Abstract: Land use-land cover change (LULCC) is driven by the interplay of forcing factors that act at global, regional, and local levels. Previous studies investigated mainly the basic socioeconomic drivers of LULCC. However, these studies less considered climate change vulnerability as a potential driver. Hence, this study is aimed to assess LULCC drivers in more fragile and dynamic landscapes of the East African Rift Valley region for the period of 1986-2016. We used a combination of Remote Sensing, Geographic Inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…As stated by focus group discussion and key informant interview the woodland of the park is not only used as source energy but also used as generating alternative income by the local communities. This result is in line with Central RiftValley [85] and Malawi [115] they revealed fuelwood collection and charcoal making were the main drivers of LULC change. Resettlement program, expansion of farmland, human-induced fire, lack of land use plan, and unwise utilization were the top significant drivers of change [110].…”
Section: Drivers Of Land Use Land Cover Changesupporting
confidence: 83%
See 2 more Smart Citations
“…As stated by focus group discussion and key informant interview the woodland of the park is not only used as source energy but also used as generating alternative income by the local communities. This result is in line with Central RiftValley [85] and Malawi [115] they revealed fuelwood collection and charcoal making were the main drivers of LULC change. Resettlement program, expansion of farmland, human-induced fire, lack of land use plan, and unwise utilization were the top significant drivers of change [110].…”
Section: Drivers Of Land Use Land Cover Changesupporting
confidence: 83%
“…Farmland expansion as the expense of forest and woodland decline was also reported [105,106]. More studies from the central Rift Valley of dryland revealed areas of cropland doubled, grass/grazing land and bareland increased as the cost of woodland destructed between 1986 and 2016 [85,99,107]. In advance to cultivated land, a remarkable increasing trend was showed mainly at the expense of forest cover [108].…”
Section: Trends Of Land Use Land Cover Changementioning
confidence: 90%
See 1 more Smart Citation
“…The percent rate of LULC change was computed by Eq. (7) ( Duraisamy et al., 2018 ; Bekele et al., 2019 ; Asmame and Abegaz, 2017 ; Esa and Assen, 2017 ). …”
Section: Methodsmentioning
confidence: 99%
“…The qualitative analysis method can only analyze the impact of various influencing factors on LULC change, but cannot quantitatively express the impact degree of various factors on LULC change [27,28]. Although the quantitative method can clarify the influence degree of various influencing factors on land use change, both methods ignore the relationship between influencing factors and land use change in spatial location [29,30], so it is difficult to accurately analyze their internal change potential mechanism. The geographic detector is a statistical method based on the statistical principle to detect spatial differentiation and reveal driving factors [31,32].…”
Section: Introductionmentioning
confidence: 99%